Medical treatment of asymptomatic chronic aortic regurgitation. (September 2011) - Lin, Aaron; Stewart, Ralph
Chronic aortic regurgitation results in left ventricular (LV) dilation, increased LV work and, eventually, a decline in LV function and heart failure. An important question is whether pharmacological therapy could preserve LV function and delay the need for aortic valve replacement. Vasodilators have a number of theoretical advantages. By lowering blood pressure, they reduce the regurgitant volume and decrease LV afterload. This article summarizes the clinical studies that have evaluated vasodilators in asymptomatic patients with chronic aortic regurgitation. Some studies suggest favorable effects on LV function and clinical outcomes, but results are inconsistent, making it difficult to draw definite conclusions. In general, studies have been too small to reliably evaluate the overall benefits and risks of this treatment, and in several studies there was no significant difference in measured blood pressure by treatment allocation. For these reasons, decisions on whether vasodilators are indicated in individual patients must currently be based on clinical judgment alone.